Multimodal Diagnostic Workup of Primary Pericardial Mesothelioma: A Case Report - Liu, Jiahui; Wang, Zhi; Yang, Ying; Xiong, Yan; Wang, Wei; Qiu, Jianxing; Zhao, Kai; Zheng, Bo (Frontiers in Cardiovascular Medicine, 2021)
Background: Primary pericardial mesothelioma (PPM) is an extremely rare tumor, and early identification and accurate diagnosis may improve its clinical outcome. Case presentation: We herein report a case of a 70-year-old woman who presented with dyspnea. Conventional transthoracic echocardiography showed massive pericardial effusion. Contrast-enhanced ultrasonography revealed a hyperenhancing mass in the pericardium. Further imaging methods, including cardiac magnetic resonance imaging and positron emission tomography/computed tomography, showed invasion of the pericardial mass into the adjacent tissues and distant metastases. Pathologic examination of a puncture biopsy specimen finally confirmed the diagnosis of PPM. Conclusion: Pericardial masses are difficult to detect when a large amount of pericardial effusion is present and the mass is small. Combination of multiple modalities plays a meaningful role in identifying PPM.